Upaya Kontribusi Melalui Keterlibatan Pengabdian Mahasiswa dalam Proses Pekerjaan Shotcrete Lereng Tunnel /Terowongan Samarinda - Pratiwi, Dheka Shara; Haekal, Muhammad; Agustina, Fitriyati; Asnan, Muhammad Noor; Pamungkas, Pulung Priyo (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
This community service project engaged Civil Engineering students and faculty from Universitas Muhammadiyah Kalimantan Timur (UMKT), in collaboration with PT Ciriajasa CM, in a two-month partnership on the Samarinda Tunnel Project. The program provided students with a platform to integrate classroom theory with real-world practice, specifically focusing on the application of shotcrete methods for slope stabilization in challenging tunnel environments. Through a partnership with industry experts, students implemented high-pressure shotcrete techniques aimed at enhancing slope stability, supporting structural durability, and contributing to sustainable infrastructure development. Using a participatory observation approach, students conducted field observations, interviews, and theoretical-to-practical comparisons, culminating in a comprehensive analysis of shotcrete quality testing at UMKT’s laboratory. This project not only advanced students' technical skills but also highlighted the significance of academic-industry collaboration in merging theoretical knowledge with applied fieldwork for sustainable construction practices.